The effects of leaves' Hydro-Alcoholic Extract Vaginal Cream and Clotrimazole on in Wistar Rats - Azam Honarmandpour; Mahnaz Fatahinia; Amir Masoud Keshavarzzade; Forogh Namjoyan; Elham Maraghi; Hossein Kamali (SAGE Publishing, 2022)
Background: In vitro, Ziziphus Spina-Christi (ZSC) leaves have been shown to have antimicrobial and antifungal effects. This study aimed to examine the effects of Ziziphus Spina leaves hydro-alcoholic extracts with Clotrimazole against Candida albicans in female rats. Methods: Four groups of rats were infected vaginally with C. Albicans, and 1 group not infected was considered negative control. The infected groups received the following treatments: 2 groups were treated with vaginal 5%, or 10%, of Ziziphus Spina extract creams. One group received 1% clotrimazole, and 1 group did not receive any treatment considered a positive control. Results: The mean number of colony-forming units (CFUs) before the intervention was 195.83 ± 395.126 in the 5% ZSC group, 346.33 ± 396.719 in the 10% ZSC group, 345.17 ± 507.431 in the clotrimazole group, 212.20 ± 148.304 in the positive control group ( P = .604), and 0 in the negative control group ( P = .003). After 1 week, the average number of CFUs considerably dropped to 65.14 ± 36.03 in the 5% ZSC group, 1.43 ± 3.60 in the 10% ZSC group, and 0.43 ± 1.13 in the clotrimazole group. The number in the positive control group remained unchanged (212.20 ± 148.304) ( P = .005). After 2 weeks, the average number of CFUs was 0 in the 10% ZSC group, Clotrimazole and negative control groups and was 4.57 ± 23.99 in the 5% ZSC group ( P < .001). Conclusions: Our findings indicated that the effectiveness of Vaginal creams containing 10% Ziziphus Spina is similar to Clotrimazole in eliminating C. Albicans.